1997
DOI: 10.1046/j.1365-2567.1997.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of B‐cell translocation gene‐1 expression by prostaglandin E2 in macrophages and the relationship to proliferation

Abstract: Although prostaglandin (PG) E2 is known to suppress various macrophage functions, the molecular mechanisms by which that occurs are largely unknown. To understand better those mechanisms, differential screening of a cDNA library from PGE2‐treated macrophages was performed. Subsequently, the DNA sequence of a differentially expressed cDNA clone was determined and the cDNA was identified as B‐cell translocation gene‐1 (BTG1), a recently cloned antiproliferative gene. A two‐ to threefold increase in macrophage BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…To determine whether the lack of CD47 preserves proliferative capacity, Jurkat T cells were plated in complete medium and exposed to a 20 Gy dose of radiation. WT and CD47 − Jurkat cells showed no difference in crystal violet staining 17,18 at time 0 and similar 4-fold increases in cell numbers at day 10. On the other hand, irradiated cultures of WT cells showed only a 1.5-fold increase in proliferative capacity vs. a 4-fold increase in proliferative capacity in cells that lack CD47 (Fig.…”
Section: Deficiency Of Cd47 Increases Radioprotection Of Jurkat T Cellsmentioning
confidence: 84%
See 1 more Smart Citation
“…To determine whether the lack of CD47 preserves proliferative capacity, Jurkat T cells were plated in complete medium and exposed to a 20 Gy dose of radiation. WT and CD47 − Jurkat cells showed no difference in crystal violet staining 17,18 at time 0 and similar 4-fold increases in cell numbers at day 10. On the other hand, irradiated cultures of WT cells showed only a 1.5-fold increase in proliferative capacity vs. a 4-fold increase in proliferative capacity in cells that lack CD47 (Fig.…”
Section: Deficiency Of Cd47 Increases Radioprotection Of Jurkat T Cellsmentioning
confidence: 84%
“…Proliferative capacity was determined as described previously. 17,18 Briefly, 2 × 10 5 cells were plated in 24-well plates in complete media and either exposed to 10 Gy IR or left untreated as controls. Ten days after radiation treatment, cells were harvested by centrifugation, and medium was removed and the well washed with 1X PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments with the forced expression of the gene showed that BTG1 negatively regulates cell proliferation (16). The antiproliferative properties of BTG1 have been observed in many different cell types including PBMC (16), testis (17), and macrophages (18). Especially, in macrophages, we and others have found that the levels of BTG1 expression negatively correlate with cell proliferation (18) and that the gene expression colocalizes with an apoptotic marker (19).…”
mentioning
confidence: 95%
“…Both BTG1 and BTG2 are preferentially expressed in quiescent cells, and overexpression of these genes causes a decrease in the growth rate and clonability of NIH 3T3 cells (2). A negative correlation between BTG1 mRNA expression and cell proliferation has been observed in, for example, T lymphocytes, macrophages, and testis development (2,5,6). BTG2 is also implicated in the control of the cell cycle.…”
mentioning
confidence: 99%